1997
DOI: 10.1097/00003246-199710000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oxygenation during warming after cardiopulmonary bypass

Abstract: The study confirms other studies showing that jugular venous desaturation can occur during rewarming after cardiopulmonary bypass surgery. Presently, SjvO2 appears to be a better monitor of cerebral oxygenation than NIRSO2. However, NIRSO2 has promise as a noninvasive monitor of cerebral oxygenation if future developments allow more quantitative measurements of oxygen saturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 28 publications
2
64
0
1
Order By: Relevance
“…Furthermore, poor agreement between the two methods of cerebral oxygenation were detected in head injury patients 18,19 as well as in patients resuscitated from cardiac arrest. 20 Sapire et al 21 found a good correlation (r2=0.63, P <0.001) between the changes from baseline of SjO 2 and regional oxygenation monitored by another NIRS (RunMan, NIM, Philadelphia, PA) device. Yet, correlation was poor in some patients, and in others, there was a delay between the two measurements.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, poor agreement between the two methods of cerebral oxygenation were detected in head injury patients 18,19 as well as in patients resuscitated from cardiac arrest. 20 Sapire et al 21 found a good correlation (r2=0.63, P <0.001) between the changes from baseline of SjO 2 and regional oxygenation monitored by another NIRS (RunMan, NIM, Philadelphia, PA) device. Yet, correlation was poor in some patients, and in others, there was a delay between the two measurements.…”
Section: Discussionmentioning
confidence: 94%
“…Yet, correlation was poor in some patients, and in others, there was a delay between the two measurements. 21 The authors also suggested that this time difference might be a result of the difference between regional oxygenation in the area of the brain monitored by NIRS and the global oxygen saturation measured by jugular bulb catheter.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from Sapire et al ., 11 who reported an increase in V-A lactate difference during the rewarming period in hypothermic CPB (15°C-33°C). This increase in V-A lactate difference was related to the decrease of SjvO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…While Kadoi et al 34 found that NIRS was more effective in detecting brain desaturation than SjVO 2 at certain stages of normothermic and hypothermic CABG and suggested that one should not rely solely on SjVO 2 during cardiopulmonary bypass (CPB), others 24,27,48 considered NIRS less sensitive than SjVO 2 . The sole randomized controlled trial 63 performed did not ascertain any difference in the number of neurological complications between patients who underwent NIRS monitoring and those who did not.…”
Section: Clinical Efficacy Of Nirs In Heart Surgerymentioning
confidence: 99%